2022
DOI: 10.3389/feduc.2022.884709
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Multimedia Presentations Through Digital Storytelling for Sustainable Development of EFL Learners’ Argumentative Writing Skills, Self-Directed Learning Skills and Learner Autonomy

Abstract: The present study explored the impact of online digital storytelling on developing EAP students’ argumentative writing skills, and its impact on improving self-directed learning skills and learner autonomy in language learning. To reach such ends, a standardized pretest and posttest in argumentative writing skills were designed, which depends on the writing tasks of IELTS task 2 and Independent TOEFL test writing tasks. Also, the self-rating scale of self-directed learning and language Learner Autonomy Scale (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 113 publications
1
2
0
2
Order By: Relevance
“…The research findings align with several studies (DeLenardo et al, 2019;Kim, 2014;Ponhan et al, 2020;Salem, 2022) Multiple studies have reached similar conclusions to those uncovered by the second research aim (Hava, 2021;Liu et al, 2018;Kasami, 2017;Kristiawan et al, 2022), which demonstrated that learners' motivation was enhanced through DST. Kristiawan et al (2022) examined the efficacy of digital narrative, influenced by the pupil's native culture, in the English language instruction of 30 junior high school students.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The research findings align with several studies (DeLenardo et al, 2019;Kim, 2014;Ponhan et al, 2020;Salem, 2022) Multiple studies have reached similar conclusions to those uncovered by the second research aim (Hava, 2021;Liu et al, 2018;Kasami, 2017;Kristiawan et al, 2022), which demonstrated that learners' motivation was enhanced through DST. Kristiawan et al (2022) examined the efficacy of digital narrative, influenced by the pupil's native culture, in the English language instruction of 30 junior high school students.…”
Section: Discussionsupporting
confidence: 88%
“…Students who engage in SDL must develop the knowledge and abilities to recognize and assess their learning requirements, reflect on what they have learned, and handle information critically and effectively (Patterson et al, 2002;Acar et al, 2015). Salem (2022) investigated how online DST affected the growth of argumentative writing abilities among EAP students and enhanced student autonomy and SDL abilities.…”
Section: Dst and Sdl Skillsmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-directed learning merupakan model proses belajar yang menitikberatkan pada kemampuan individu untuk memahami materi pembelajaran secara mandiri (Salem, 2022).…”
unclassified
“…Salah satu bentuk media pembelajaran adalah multimedia. Multimedia pembelajaran adalah media yang menggabungkan elemen teks, audio, video, dan sebagainya (Salem, 2022).…”
unclassified